Localization and connections of the tail of caudate and caudal putamen in mouse brain - Ma, Run-Zhe; Chen, Sheng-Qiang; Zhu, Ge; Cai, Hui-Ru; Zhang, Jin-Yuan; Peng, Yi-Min; Lian, Dian; Ding, Song-Lin (Frontiers in Neural Circuits, 2025)
The neural circuits of the striatum (caudate and putamen) constitute a crucial component of the extrapyramidal motor system, and dysfunction in these circuits is correlated with significant neurological disorders including Parkinson’s disease and Huntington’s disease. Many previous studies in rodents revealed the neural connections of the rostral and intermediate parts of the striatum, but relatively fewer studies focused on the caudal striatum, which likely contains both the tail of caudate (CaT) and caudal putamen (PuC). In this study, we investigate the gene markers for the CaT and PuC and brain-wide afferent and efferent projections of the caudal striatum in mice using both anterograde and retrograde neural tracing methods. Some genes such as prodynorphin, otoferlin, and Wolfram syndrome 1 homolog are strongly expressed in CaT and PuC while some others such as neurotensin are almost exclusively expressed in CaT. The major afferent projections of the CaT originate from the substantia nigra (SN), ventral tegmental area, basolateral amygdala, parafascicular nucleus, and visual, somatosensory, auditory and parietal association cortices. The PuC receives its main inputs from the posterior intralaminar nucleus, ventroposterior medial nucleus (VPM), medial geniculate nucleus, and entorhinal, motor and auditory cortices. Both CaT and PuC neurons (including dopamine receptor 1 expressing ones) project in a rough topographical manner to the external and internal divisions of globus pallidus (GP) and SN. However, dopamine receptor 2 expressing neurons in nearly all striatal regions (including CaT and PuC) exclusively target the external GP. In conclusion, the present study has identified the mouse equivalent of the primate CaT and revealed detailed brain-wide connections of the CaT and PuC in rodent. These findings would offer new insights into the functional correlation and disease-related neural circuits related to the caudal striatum.